(untitled) (Research, Society and Development, 2020)
Plantago major (PM) is a plant rich in chemical compounds that ensure it a wide spectrum of use around the world. Recent studies have advanced when studying the relationship of the plant with antimicrobial and antibiofilm actions. Therefore, the aim of the present study is to evaluate the antimicrobial and antibiofilm activity of the Plantago major species. For this, a literatura search was performed in the PubMed, LILACS and SciELO databases, using the term “Plantago major” in combination with the descriptors MeSH and DeCS “Dentistry” and “Anti-infective agents”, associated with each other by the operator boolean AND and adapted for each database. In addition, a complementary search was made on Google Scholar. A total of 130 results were found. After a critical reading of titles and abstracts, 16 studies were selected. The review includes studies published in the last 20 years that addressed the species Plantago major with antimicrobial and antibiofilm action in dentistry. PM has components that act with antimicrobial and antibiofilm potential. The plant extract has a spectrum of action in vitro against Streptococcus mutans, Pseudomonas aeruginosa, Bacillus subtilis, Shigella dysenteriae and Lactobacillus acidophilus. However, there is no consensus in the literature on the action of PM on the growth of Candida albicans, Staphylococcus aureus, Porphyromonas gingivalis and Escherichia coli. Therefore, PM has a good antimicrobial activity in vitro, in biofilm bacteria, however further studies are needed to elucidate the action against other bacteria and its clinical applicability.